ASSOCIATION OF SMOKING AND BLADDER CANCER: AN UPDATED SYSTEMATIC REVIEW - Amal Ramadhani, Rizkia; Fithri Rofifa, Amira (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Introduction: Bladder cancer is the 10th most common global cancer, with increasing incidence, primarily linked to smoking, occupational exposures, and genetic factors. This systematic review explores the association between tobacco use and bladder cancer, emphasizing the importance of understanding its multifactorial etiology for effective prevention. Method: The researchers in this study followed the 2020 Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines to ensure that their work met the required standards. This was done to ensure the precision and reliability of the conclusions derived from the research. Result: Our search produced 18 results. After looking at the titles and summaries, we found several papers that fit our criteria. At first, we excluded few articles because they were written in review and case report style. But after reading the full papers carefully, we included five papers in our final analysis. These papers included two-sample univariable and multivariable Mendelian Randomization (MR) analysis, case control study, prospective cohort study of patients with NMIBC diagnosed from 2015 to 2019, experimental study, and rtrospective study. Conclusion: The systematic review involved Mendelian Randomization analysis, underscores smoking as a significant risk factor for bladder cancer, with no evidence linking alcohol consumption to the disease. In a prospective cohort study on Non-Muscle Invasive Bladder Cancer, the study establishes a dose-dependent relationship, emphasizing the urgency for effective smoking cessation interventions in patients, especially those with prolonged smoking history. Additionally, the investigation into molecular pathways reveals the upregulation of the platelet-activating factor (PAF) pathway by cigarette smoke exposure, suggesting PAF-PAF receptor (PAF-R) interaction as a promising therapeutic target for managing bladder cancer growth.